A Career success of Master of Arts in Education graduates of Naga College Foundation - Villanueva, Josephine Francia; Nolasco, Michael N.; Cruz, Juan O. (Universitas Ahmad Dahlan, 2025)
This study assessed the academic writing competence of graduate students at Naga College Foundation, Inc. (NCF) to inform an intervention program enhancing thesis and dissertation writing for SY 2024–2025. It analysed graduates' socio-demographic profiles, employment and promotion status, developed competencies and values, and their relationship to career outcomes. A descriptive-correlational design was used, involving 50 Master of Arts in Education (MAEd) graduates from 2017 to 2024: a researcher-made questionnaire collected data, analysed using weighted mean, Pearson correlation, and coefficient of determination. Most graduates were aged 36–40 or above (34% each), female (66%), and married (79%). The 2023–2024 cohort was the most significant (40%). Employment was high (98%), with 66% in top academic positions. Competency scores were highest in human relations (3.82) and lowest in research (3.45). Correlation analysis showed positive relationships between competencies/values and promotion and employment, with r-values ranging from 0.26 to 0.70. Critical thinking (r² = 0.44) had the most potent effects. MAEd graduates demonstrated strong employability and career growth potential, backed by competencies in interpersonal, problem-solving, and technological skills. NCF MAEd graduates are mature, competent, and values-driven professionals with strong employment outcomes and leadership roles. Enhancement programs should strengthen research skills and critical thinking while sustaining human relations and value-based education to support career advancement. The results of this study imply that the MAEd program at NCF needs to design targeted interventions to strengthen research and critical thinking skills to enhance graduates' competitiveness and career mobility further.